2018
DOI: 10.1021/acsnano.8b04433
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Permeability and Retention-like Extravasation of Nanoparticles from the Vasculature into Tuberculosis Granulomas in Zebrafish and Mouse Models

Abstract: The enhanced permeability and retention (EPR) effect is the only described mechanism enabling nanoparticles (NPs) flowing in blood to reach tumors by a passive targeting mechanism. Here, using the transparent zebrafish model infected with Mycobacterium marinum we show that an EPR-like process also occurs allowing different types of NPs to extravasate from the vasculature to reach granulomas that assemble during tuberculosis (TB) infection. PEGylated liposomes and other NP types cross endothelial barriers near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 66 publications
1
98
0
Order By: Relevance
“…A zebrafish embryo model of neural tube granulomas was established according to the method described by Griffiths's group. [51] We established the infection by injecting ≈250 colony-forming units (c.f.u.) of green fluorescent protein-expressing Mycobacterium marinum (GFP-M.m) into the neural tube of the zebrafish embryo at 36 h post-fertilization (hpf).…”
Section: In Vivo Granuloma-targeting Imaging In a Zebrafish Embryo Nementioning
confidence: 99%
See 1 more Smart Citation
“…A zebrafish embryo model of neural tube granulomas was established according to the method described by Griffiths's group. [51] We established the infection by injecting ≈250 colony-forming units (c.f.u.) of green fluorescent protein-expressing Mycobacterium marinum (GFP-M.m) into the neural tube of the zebrafish embryo at 36 h post-fertilization (hpf).…”
Section: In Vivo Granuloma-targeting Imaging In a Zebrafish Embryo Nementioning
confidence: 99%
“…This structure is situated on the dorsal side of the embryo, above the notochord and below the dorsal longitudinal anastomotic vessel. [51] During the later stages of infection, between 3 and 5 days post-infection (dpi), the granuloma progresses, causing the release of infected tissues and a large amount of M.m (named discharge) into the medium and ultimately leaving a cavity at 7 dpi ( Figure 6A). This morphological change is highly reminiscent of the changes in granulomas in the lungs of pulmonary TB patients, where bacteria are released from the necrotic center of the granulomas.…”
Section: In Vivo Granuloma-targeting Imaging In a Zebrafish Embryo Nementioning
confidence: 99%
“…It was reported that PEGylated drugs may also possess enhanced permeability and retention (EPR) effect, which will benefit the PEG‐modified drugs accumulating in the tumor tissue [40]. Since the vascular permeability in tumor tissue is greater than that in healthy tissue, which further improves the delivery efficiency of these nano‐scaled PEGylated drugs [41–46]. Due to the biological and technological superiorities, PEGylated pharmaceuticals generally showed a better efficiency and lower systemic side effect.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1940s, the ring‐opening polymerization (ROP) of N ‐carboxyanhydrides (NCAs) derived from α‐amino acids has offered the most facile synthetic approach in producing synthetic polypeptides with controlled molecular weights and low polydispersities . In more recent times, the incorporation of poly(α‐peptoid)s based on N ‐substituted glycine (i.e., sarcosine) into polypeptide‐based materials via NCA‐ROP has been widely investigated owing to their potential as naturally derived “stealth polymers.” Poly(sarcosine), the most widely investigated amino acid‐derived polypeptoid, has been of particular interest in the biomedical field due to its poly(ethylene glycol) (PEG) properties (i.e., hydrophilicity, limited non‐specific organ uptake, extended circulation times etc. ), indicating its potential as a replacement for PEG .…”
Section: Introductionmentioning
confidence: 99%